Primate Pulpal Healing after Exposure and TheraCal Application - Cannon, M.; Gerodias, N.; Vieira, A. [UNESP]; Percinoto, Célio [UNESP]; Jurado, R. (Journal Pedodontics Inc, 2014)
Aim: The purpose of this in vivo study was to compare the effectiveness of a new light cured resin based dicalcium/tricalcium silicate pulp capping material (TheraCal LC, Bisco), pure Portland cement, resin based calcium hydroxide or glass ionomer in the healing of bacterially contaminated primate pulps. Study design: The experiment required four primates each having 12 teeth prepared with buccal penetrations into the pulpal tissues with an exposure of approximately 1.0 mm. The exposed pulps of the primate teeth were covered with cotton pellets soaked in a bacterial mixture consisting of microorganisms normally found in human pulpal abscesses. After removal of the pellet, hemostasis was obtained and the pulp capping agents applied. The light cured resin based pulp capping material (TheraCal LC) was applied to the pulpal tissue of twelve teeth with a needle tip syringe and light cured for 15 seconds. Pure Portland cement mixed with a 2% Chlorhexidine solution was placed on the exposed pulpal tissues of another twelve teeth. Twelve additional teeth had a base of GIC applied (Triage, Fuji VII GC America) and another twelve had a pulp cap with VLC DYCAL (Dentsply), a light cured calcium hydroxide resin based material. The pulp capping bases were then covered with a RMGI (Fuji II LC GC America). The tissue samples were collected at 4 weeks. The samples were deminerilized, sectioned, stained and histologically graded. Results: There were no statistically significant differences between the groups in regard to pulpal inflammation (H= 0.679, P=1.00). However, both the Portland cement and light cured TheraCal LC groups had significantly more frequent hard tissue bridge formation at 28 days than the GIC and VLC Dycal groups (H= 11.989, P=0.009). The measured thickness of the hard tissue bridges with the pure Portland and light cured TheraCal LC groups were statistically greater than that of the other two groups (H= 15.849, P=0.002). In addition, the occurrence of pulpal necrosis was greater with the GIC group than the others. Four premolars, one each treated according to the protocols were analyzed with a microCT machine. The premolar treated with the light cured TheraCal LC demonstrated a complete hard tissue bridge. The premolar treated with the GIC did not show a complete hard tissue bridge while the premolar treated with VLC Dycal had an incomplete bridge. The pure Portland with Chlorhexidine mixture created extensive hard tissue bridging.Conclusion: TheraCal LC applied to primate pulps created dentin bridges and mild inflammation acceptable for pulp capping.
Keywords: pulp exposures; pulp response; bacteria; primate